Genetic and biochemical characterization of kirromycin resistance mutations in Bacillus subtilis. - Smith, I (1978)
Spontaneous mutations causing resistance to the EF-Tu-specific antibiotic kirromycin have been isolated and mapped in Bacillus subtilis. Three-factor transductional and transformational crosses have placed the kir locus proximal to ery-1 and distal to strA (rpsL) and several mutations affecting elongation factors EF-G and EF-Tu, in the order: cysA strA [fus-1/ts-6(EF-G)] [ts-5(EF-Tu)] kir ery-1 spcA. Purified EF-Tu from mutant strains is more resistant to kirromycin as measured by in vitro protein synthesis and also shows a more acidic isoelectric point than wild-type EF-Tu. This indicates that the kir locus is the genetic determinant (tuf) for EF-Tu and that there is a single active gene for this enzyme in B. subtilis.